Adhesive composition and adhesive tape
An acrylic adhesive composition with a tailored acrylic copolymer and crosslinking agent addresses the challenges of adhesion and performance on POM and other 5G-related resin materials, offering enhanced adhesion and durability for electronic devices and sensors.
Patent Information
- Application Number
- JP2023510088
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-03-31
AI Technical Summary
Existing adhesive compositions and tapes struggle with adhesion to poorly adhesive engineering plastics like POM, and they lack sufficient high temperature retention, load resistance, and impact resistance, especially in the context of 5G technology where materials with less transmission loss are used.
The development of an acrylic adhesive composition containing an acrylic copolymer with specific molecular weight and monomer composition, along with a crosslinking agent, which enhances adhesion, high temperature retention, load resistance, and impact resistance, even on difficult-to-adhere resins such as POM.
The proposed adhesive composition and tape exhibit excellent adhesion, high temperature retention, load resistance, and impact resistance, making them suitable for fixing portable electronic devices, automobile sensors, and dashcams, particularly on resin materials used in 5G applications.
Smart Images

Figure 0007671841000009 
Figure 0007671841000010 
Figure 0007671841000011
Abstract
Description
[Technical field]
[0001] The present invention relates to an acrylic pressure-sensitive adhesive composition and adhesive tape having adhesive properties, high-temperature retention, load-bearing property and impact resistance, which have been developed for the purpose of fixing portable electronic devices such as smartphones and tablet terminals, as well as automobile sensors and drive recorders, etc., and which have improved adhesive properties due to properties including tack, and which have excellent adhesion to resin materials that will be used in conjunction with the practical application of 5G, particularly poorly adhesive resin materials such as POM (polyoxymethylene; polyacetal). [Background technology]
[0002] In recent years, the practical application of 5G, the next-generation mobile communication system after 4G, has progressed rapidly. 5G stands for "5th Generation (fifth generation mobile communication system)." 5G will enable high-speed, large-capacity communication, highly reliable, low-latency communication, and simultaneous connection to multiple devices by using previously unused high-frequency bands above 20 GHz and a super-multiple-element antenna called "MIMO (Multiple-Input and Multiple-Output)." However, because 5G uses higher frequencies of radio waves, transmission loss due to antennas, wiring, etc. tends to be greater than that of 4G. Since transmission loss leads to a decrease in terminal performance, the use of materials with properties that cause less transmission loss than in previous products, such as fluororesin, liquid crystal polymers, and low dielectric polyimides, in the components that make up 5G is progressing. In fact, development of resin films for circuit boards using these materials is underway, and in some cases they are being adopted as components for 5G terminals. In addition, as the frequency increases, the radio waves tend to travel in a more directional direction, and the radio waves that can be received indoors or in the shadows of buildings become weaker, resulting in locations where it becomes difficult for a terminal to connect to a network, etc. As a result, the performance requirements for materials are also changing. For example, there are attempts to increase the proportion of metal used in the body of devices to be replaced with plastic or glass, which allow radio waves to pass through more easily.
[0003] Conventionally, adhesives and adhesive tapes developed for use in fastening portable electronic devices such as smartphones and tablet devices, as well as automobile sensors and dashcams, have required adhesion, high temperature retention, load resistance, impact resistance, and waterproofing. However, adhesive tapes that are specialized for such characteristics have weak tack on the surface of the adhesive layer, and while they have excellent adhesion to metal, they have poor adhesion to resin materials, especially poorly adhesive resin materials such as POM, and may not be able to demonstrate their properties when used with resin materials suitable for 5G such as those mentioned above.
[0004] Pressure-sensitive adhesive compositions of various compositions have been investigated for use in pressure-sensitive adhesive tapes to be applied to poorly adhesive adherends. In Patent Document 1, in view of the recent trend of replacing metal-based materials with plastic-based materials in automobiles and the like, a pressure-sensitive adhesive composition is provided that can form a pressure-sensitive adhesive layer having high stress relaxation properties in a high-temperature environment and high adhesion to a low-polarity adherend while maintaining tackiness and cohesive strength required for adhesive properties. This pressure-sensitive adhesive composition contains a (meth)acrylic copolymer (A) having an acid value of 7.8 to 45, a rosin-based tackifier resin (B) having a softening point of 100°C or higher, and a crosslinking agent (C). The (meth)acrylic copolymer (A) is a copolymer of monomer components including a (meth)acrylic acid alkyl ester having an alkyl group with less than 8 carbon atoms, a (meth)acrylic acid alkyl ester having an alkyl group with 8 or more carbon atoms, and an acidic group-containing monomer. This pressure-sensitive adhesive composition contains more than 16 parts by mass and less than 30 parts by mass of the rosin-based tackifier resin (B) and 0.01 to 5 parts by mass of the crosslinking agent (C) relative to 100 parts by mass of the (meth)acrylic copolymer (A). In Patent Document 1, polyolefin resins such as polypropylene and polyethylene are listed as materials for forming a low-polarity adherend for evaluating adhesiveness.
[0005] In recent years, in order to improve the antifouling properties and to emphasize design, materials that are difficult to adhere with existing adhesives, such as oil- or water-repellent coated painted surfaces, have been increasingly used in electronic devices, and in Patent Document 2, an acrylic adhesive having excellent adhesion to difficult-to-adhere adherends and impact resistance and an adhesive sheet for electronic devices using the same are provided, in consideration of this situation. This acrylic adhesive contains 100 parts by weight of an acrylic copolymer having a molecular weight distribution (Mw / Mn) of 8 to 23 and 15 to 25 parts by weight of a tackifier resin having a softening point of 140°C or lower. In Patent Document 2, a "difficult-to-adhere substrate" is defined as a substrate made of a non-polar resin or a substrate whose surface has been subjected to a non-polar surface treatment, and specific examples include materials that have been fluorine-coated for oil or water repellency, polyethylene, polypropylene, etc.
[0006] Patent Document 3 provides a pressure-sensitive adhesive composition for poorly adhesive substrates that adheres firmly to poorly adhesive substrates and has high retention power. This pressure-sensitive adhesive composition contains an acrylic resin (A) obtained by copolymerizing a terminal carboxyl group-containing monomer (a1) represented by the following general formula (1) and a copolymerization component (a) containing (meth)acrylic acid (a2). [Formula] CH2=CR 1 -CO-O-(R 2 -COO-)nH···(1) (where R 1 is hydrogen or a methyl group, R 2 represents a saturated aliphatic, unsaturated aliphatic, aromatic, saturated alicyclic, or divalent unsaturated alicyclic hydrocarbon, and n represents a positive number of 1 or more.) Patent Document 3 lists ethylene propylene diene rubber (EPDM), butyl rubber (IIR), chloroprene rubber (CR), styrene butadiene rubber (SBR), thermoplastic polyolefin rubber, and modified asphalt as examples of materials that form poorly adhesive adherends. However, the poorly adhesive substrates in Prior Art Document 3 do not include POM (polyacetal), which is one of the engineering plastics with excellent heat resistance and mechanical properties and is used in rotating parts such as gears and bearings, parts that require durability such as grips, hooks, and covers, and musical instruments. In Patent Document 4, a pressure-sensitive adhesive used for attaching a decorative sheet such as wallpaper to a wall material or panel is required to have sufficient adhesive strength and to be reappliable by repositioning, and is desired to have so-called tackiness. In consideration of this, a pressure-sensitive adhesive composition is provided that has high adhesive strength, tackiness, reapplicability, and does not impair dimensional stability after the attachment process. This pressure-sensitive adhesive composition contains an acrylic resin copolymer in which n-butyl acrylate, a carboxyl group-containing monomer, and a hydroxyl group-containing monomer are polymerized. The proportion of n-butyl acrylate in 100 parts by mass of the acrylic resin copolymer is 20 parts by mass or more, and the proportion of the hydroxyl group-containing monomer is 0.05 to 5.0 parts by mass. The acid value of this acrylic resin copolymer is 40 to 80 mgKOH / g, the mass average molecular weight is 200,000 to 500,000, and the polydispersity (Mw / Mn) is 2.0 or less. In Patent Document 4, with regard to the materials of wall materials, panels, and decorative sheets to which the pressure-sensitive adhesive composition is applied, examples of wall material and panel materials include aluminum, stainless steel, gypsum board, galvanized steel sheet, resin-coated steel sheet, etc., and examples of decorative sheet materials include polyvinyl chloride, polyethylene terephthalate, olefin, etc. Patent Document 5 provides an adhesive composition and an adhesive tape using the same, which are excellent in repulsion resistance, load resistance, narrow-frame moisture and heat load resistance, processability, impact resistance and waterproofness and can withstand the repulsive force of an FPC from the inside and can also withstand external forces such as impact resistance and waterproofness in order to fix the housing-LCD-top panel of the display screen of portable electronic devices such as smartphones and tablet terminals, which are becoming larger and the housings are becoming thinner. The adhesive composition described in Patent Document 5 contains an acrylic copolymer (A), a crosslinking agent (B), a silane coupling agent (C), and an antioxidant (D). The acrylic copolymer (A) contains 10 to 20 mass% of a (meth)acrylic acid alkyl ester (A1) having an alkyl group with 1 to 3 carbon atoms, 50 to 80 mass% of a (meth)acrylic acid alkyl ester (A2) having an alkyl group with 4 to 12 carbon atoms, 10 to 15 mass% of a carboxyl group-containing monomer (A3), 0.01 to 0.5 mass% of a hydroxyl group-containing monomer (A4), and 1 to 5 mass% of vinyl acetate (A5) as polymer chain components. The acrylic copolymer (A) is obtained by polymerization using a peroxide-based polymerization initiator, and has a weight average molecular weight of 950,000 to 2,000,000 and a theoretical Tg of -55°C or less. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-177902 A [Patent Document 2] JP 2019-214739 A [Patent Document 3] JP 2019-151837 A [Patent Document 4] JP 2020-158590 A [Patent Document 5] Patent No. 6307175 Summary of the Invention [Problem to be solved by the invention]
[0008] Patent Documents 1 to 5 contain no description or suggestion whatsoever regarding the adhesiveness of pressure sensitive adhesives to adherends made of poorly adhesive engineering plastics such as POM. Furthermore, Patent Document 4 is silent about the holding power of the pressure-sensitive adhesive to a low-polarity adherend. Moreover, Patent Document 5 does not consider the tack of the adhesive. Therefore, an object of the present invention is to provide an acrylic pressure-sensitive adhesive composition and a pressure-sensitive adhesive tape that have excellent adhesion, high-temperature retention, load resistance and impact resistance, even to poorly adhesive resins such as POM, by improving the adhesion based on properties including tack on the surface of the pressure-sensitive adhesive layer compared to conventional pressure-sensitive adhesive tapes. A further object of the present invention is to provide an acrylic adhesive composition and adhesive tape which have excellent adhesion, high temperature retention, load resistance and impact resistance and which have been developed for the purpose of fixing portable electronic devices such as smartphones and tablet terminals, automobile sensors, drive recorders and the like, and which have improved adhesion due to properties including tack, and which have excellent adhesion to resin materials which will be used in conjunction with the practical application of 5G, particularly poorly adhesive resins such as POM. [Means for solving the problem]
[0009] As a result of intensive research to achieve the above object, the present inventors have found that by using an acrylic copolymer selected in consideration of adhesion based on properties including tack as the resin component of a pressure-sensitive adhesive composition, it is possible to provide an acrylic pressure-sensitive adhesive composition and a pressure-sensitive adhesive tape using the same that have good adhesion to poorly adhesive adherends made of low-polarity resins such as POM and are excellent in high-temperature retention, load resistance, and impact resistance. The present inventors have completed the present invention based on this new finding.
[0010] The present invention includes the following aspects. [1] A pressure-sensitive adhesive composition comprising an acrylic copolymer (A) and a crosslinking agent (B), The weight average molecular weight of the acrylic copolymer (A) is 650,000 or more and 1,200,000 or less, and the monomer (A) has a Tg' (glass transition temperature when the monomer is homopolymerized) of 273 K or more and 437 K or less among all monomer components of the acrylic copolymer (A). HTg ) content is 11.5 mass% or more, The theoretical glass transition temperature (theoretical Tg) of the acrylic copolymer (A) is a, and the weight average molecular weight (× 10 4) in the total monomer components (A HTg ) is expressed as c by the following formula (1):
[0011]
number
[0012] The adhesion index expressed as 1.5 × 10 -2 Above 2.0×10 -2 Below is the Adhesive composition. [2] The pressure-sensitive adhesive composition according to [1], wherein the acrylic copolymer (A) has a theoretical Tg of 223 K or less. [3] The pressure-sensitive adhesive composition according to [1], wherein the acrylic copolymer (A) is an acrylic copolymer having a carboxyl group and a hydroxyl group. [4] The pressure-sensitive adhesive composition according to any one of [1] to [3], wherein the monomer components of the acrylic copolymer (A) include a (meth)acrylic acid alkyl ester (A1) having an alkyl group having from 4 to 12 carbon atoms, a (meth)acrylic acid alkyl ester (A2) having an alkyl group having from 1 to 3 carbon atoms, a carboxyl group-containing monomer (A3), and a hydroxyl group-containing monomer (A4). [5] The pressure-sensitive adhesive composition according to any one of [1] to [4], wherein the monomer components of the acrylic copolymer (A) comprise, based on 100 mass% of all monomer components, 50% by mass or more and 90% by mass or less of (meth)acrylic acid alkyl ester (A1) having an alkyl group having from 4 to 12 carbon atoms, 3% by mass or more and 10% by mass or less of (meth)acrylic acid alkyl ester (A2) having an alkyl group having from 1 to 3 carbon atoms, 1% by mass or more and 10% by mass or less of a carboxyl group-containing monomer (A3), and 0.1% by mass or more and 0.5% by mass or less of a hydroxyl group-containing monomer (A4). [6] The pressure-sensitive adhesive composition according to any one of [1] to [5], wherein the total content of the carboxyl group-containing monomer (A3) and the hydroxyl group-containing monomer (A4) is 10.5 mass % or less. [7] The pressure-sensitive adhesive composition according to any one of [1] to [6], wherein the monomer components of the acrylic copolymer include a vinyl compound monomer (A5) other than the monomer components (A1) to (A4). [8] The pressure-sensitive adhesive composition according to any one of [1] to [7], wherein the monomer components of the acrylic copolymer contain 10 mass % or less of a vinyl compound monomer (A5) other than the monomer components (A1) to (A4). [9] A pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of [1] to [8].
[10] The adhesive tape according to [9], comprising a sheet-like substrate and an adhesive layer provided on at least one surface of the sheet-like substrate. Effect of the Invention
[0013] According to the present invention, in an acrylic pressure-sensitive adhesive composition and adhesive tape which have been developed with the aim of fixing portable electronic devices such as smartphones and tablet terminals, as well as automobile sensors and drive recorders, and which have excellent adhesion, high-temperature retention, load-bearing and impact resistance, it is possible to provide a pressure-sensitive adhesive composition and adhesive tape which have improved adhesion due to properties including tack, and which have excellent adhesion to resin materials which will be used in conjunction with the practical application of 5G, particularly poorly adhesive resins such as POM. [Brief description of the drawings]
[0014] [Figure 1] 1(A) to 1(C) are diagrams illustrating a layer structure according to one embodiment of the pressure-sensitive adhesive tape of the present invention. [Diagram 2] FIG. 2A is a diagram showing a schematic planar shape of a test sample used in evaluating impact resistance, and FIG. 2B is a diagram showing a schematic configuration of a test device used in evaluating impact resistance. [Diagram 3] FIG. 2 is a schematic diagram for explaining a method for evaluating load resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] <Adhesive composition> The pressure-sensitive adhesive composition of the present invention contains an acrylic copolymer (A) and a crosslinking agent (B). The pressure-sensitive adhesive layer of the pressure-sensitive adhesive tape can be formed in a state in which the acrylic copolymer (A) is cured with the crosslinking agent (B). (Acrylic copolymer) The acrylic copolymer (A) has an adhesion index of 1.5×10 -2 Above 2.0×10 -2 The following acrylic copolymers are used:
[0016]
number
[0017] a: Theoretical glass transition temperature (theoretical Tg) of acrylic copolymer (A) (unit: K) b: Weight average molecular weight of acrylic copolymer (A) (× 10 4 ) c: Monomer (A) having a glass transition temperature (Tg') of 273 K or more and 437 K or less when the monomers contained in the total monomer components of the acrylic copolymer (A) are homopolymerized HTg ) content (percentage of the total monomer mass, unit %)
[0018] Important properties that affect the adhesiveness of adhesives include high temperature retention, load bearing, impact resistance, adhesive strength, and tackiness. There are various factors that affect the properties of adhesives, but in the development process, it was found that three factors, the "theoretical Tg" of the acrylic copolymer, the "weight average molecular weight" of the synthesized acrylic copolymer, and the "proportion of high Tg' monomers" in the monomer composition that constitutes the acrylic copolymer, have a significant effect on the expression of important properties of adhesives such as adhesive strength. Mainly, the "theoretical Tg" affects the compatibility with the adherend and ease of application, which are affected by tackiness, the "weight average molecular weight" affects high temperature retention, and the "proportion of high Tg' monomers" affects adhesive strength. It is not the case that the larger or smaller the factors, the better, but there are appropriate values depending on the adherend to which the desired adhesive strength is to be expressed. However, each factor is intricately intertwined and ultimately manifests as adhesiveness, and it is not easy to consider each factor independently. Therefore, in the present invention, the concept of "adhesion index" is introduced as an index that can simply and effectively comprehensively evaluate the adhesiveness expressed by these three factors. As shown in formula (1), the "adhesion index" is expressed as the reciprocal of the cube root of the product of the three factors mentioned above. A low value of this index tends to result in characteristics such as high holding power, high adhesion, and low tackiness, while a high value of this index tends to result in characteristics such as low holding power, low adhesion, and high tackiness. By setting the adhesion index within the above-mentioned specific range, it is possible to provide a pressure-sensitive adhesive composition and pressure-sensitive adhesive tape that have a good balance of the above-mentioned properties, exhibit good adhesion, and can be suitably applied to poorly adhesive substrates made of POM, etc.
[0019] The theoretical Tg of the acrylic copolymer (A) can be determined by a standard method using the FOX formula, as described in Patent Document 3. The theoretical Tg of the acrylic copolymer (A) is preferably 223 K (-50°C) or lower, more preferably 213 K or higher and 203 K or lower (-60 to -70°C). The weight average molecular weight of the acrylic copolymer (A) is preferably from 650,000 to 1,200,000, and more preferably from 700,000 to 1,100,000, from the viewpoint of achieving a good balance between adhesion, high-temperature retention, load resistance, and impact resistance, and also obtaining good adhesion to poorly adhesive resins such as POM. The weight average molecular weight can be measured by a standard method using GPC. (Monomer component) The acrylic copolymer (A) is formed by copolymerization of monomer components consisting of a plurality of different monomers, mainly utilizing (meth)acrylic groups. The acrylic copolymer (A) is preferably an acrylic copolymer having a carboxyl group and a hydroxyl group. The monomer components constituting the polymer chain of the acrylic copolymer having a carboxyl group and a hydroxyl group preferably contain the following monomers. (Meth)acrylic acid alkyl ester (A1) having an alkyl group having 4 to 12 carbon atoms (hereinafter also referred to as "component (A1)") (Meth)acrylic acid alkyl ester (A2) having an alkyl group with 1 to 3 carbon atoms (hereinafter also referred to as "component (A2)") Carboxyl group-containing monomer (A3) (hereinafter also referred to as component (A3)) Hydroxyl-containing monomer (A4) (hereinafter also referred to as "component (A4)") The monomer components of the acrylic copolymer further include A vinyl compound (A5) other than components (A1) to (A4) (hereinafter also referred to as "component (A5)" may include:
[0020] Each monomer component will be described below. In the following description, "(meth)acrylic" is a general term for acrylic and methacrylic. Component (A1) is an alkyl (meth)acrylate ester having an alkyl group having 4 to 12 carbon atoms. Specific examples include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, and lauryl (meth)acrylate. These may be used in combination of two or more. Of these, 2-ethylhexyl (meth)acrylate and isooctyl (meth)acrylate are preferred.
[0021] Component (A2) is a (meth)acrylic acid alkyl ester having an alkyl group having from 1 to 3 carbon atoms. Specific examples include methyl (meth)acrylate, ethyl (meth)acrylate, and propyl (meth)acrylate. These may be used in combination of two or more kinds. Of these, methyl (meth)acrylate and ethyl (meth)acrylate are preferred.
[0022] The component (A3) is a component that mainly contributes to improving the high temperature retention and load bearing properties by imparting an appropriate proportion of carboxyl groups to the acrylic copolymer (A). Specific examples include acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, 2-carboxy-1-butene, 2-carboxy-1-pentene, 2-carboxy-1-hexene, and 2-carboxy-1-heptene. These may be used in combination of two or more kinds. Of these, acrylic acid and methacrylic acid are preferred.
[0023] The component (A4) is a component that mainly contributes to improving the application property and retention by imparting an appropriate proportion of hydroxyl groups to the acrylic copolymer (A). Specific examples include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. These may be used in combination of two or more kinds. Among these, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferable.
[0024] Of the constituent components (monomer units) of the acrylic copolymer (A), i.e., 100% by mass of all monomer components, the content of component (A1) is preferably 50% by mass or more and 90% by mass or less, more preferably 70% by mass or more and 90% by mass or less; the content of component (A2) is preferably 3% by mass or more and 10% by mass or less, more preferably 3% by mass or more and 7% by mass or less; the content of component (A3) is preferably 1% by mass or more and 10% by mass or less, more preferably 5% by mass or more and 8% by mass or less; and the content of component (A4) is preferably 0.1% by mass or more and 0.5% by mass or less, more preferably 0.1% by mass or more and 0.2% by mass or less. The total content of components (A3) and (A4) in the total monomer components is preferably 10.5 mass % or less.
[0025] Furthermore, the monomer components of the acrylic copolymer (A) may further contain a monomer (A5) (hereinafter also referred to as "component (A5)") other than the components (A1) to (A4) within the scope that does not impair the effects of the present invention. The component (A5) may be a monomer (A HTg ) other than the components (A1) to (A4), as well as other copolymerizable monomers that are used in combination as necessary. The proportion of the component (A5) in all monomer components is preferably from 0% by mass to 10% by mass.
[0026] The monomer component of the acrylic copolymer (A) is a monomer (A) having a Tg' in a specific range of 273K or more and 437K or less. HTg ). Monomer (A HTg ) can be contained in the monomer component as at least one of the above-mentioned components (A1) to (A5). Monomer (A HTg When the monomer component of the acrylic copolymer (A) is at least one of the components (A1) to (A4), the monomer (A HTg The content (%) of the monomer (A) is used as "c" in formula (1). HTg ) is used, the sum of these content percentages is used as "c". Monomer (A HTg When the monomer component of the acrylic copolymer (A) is at least the component (A5) among the components (A1) to (A5), the monomer (A HTg The content (%) of the monomer (A) is used as "c" in formula (1). HTg ) is used, the sum of these content percentages is used as "c". Monomers (A) contained in the total monomer components of the acrylic copolymer (A) HTgThe content of ) is preferably 11.5 mass % or more, and more preferably 11.5 mass % or more and 50 mass % or less.
[0027] Monomers with Tg' of 273K or more and 437K or less (A HTg ) may include monomers having a (co)polymerizable vinyl group that is copolymerizable with other monomers. Examples of monomers having a polymerizable vinyl group with a Tg' in the above-mentioned specific range include vinyl compounds having a (meth)acryloyloxy group and a Tg' in the above-mentioned specific range, vinyl compounds having a (meth)acrylamide group and a Tg' in the above-mentioned specific range, acrylonitrile (Tg': 378K), vinyl acetate (Tg': 305K), etc., and at least one of these can be selected and used. Examples of vinyl compounds having a (meth)acryloyloxy group include (meth)acrylic acid and (meth)acrylic acid alkyl esters represented by the following formula (2) and having a Tg' in the above-mentioned specific range, and di(meth)acrylic acid alkyl esters represented by the following formula (3) and having a Tg' in the above-mentioned specific range.
[0028] [ka]
[0029] (In the formula, R 1 represents a hydrogen atom or a methyl group, and R 2 represents a hydrogen atom or an optionally substituted alkyl group. R 2 Examples of the alkyl group include an alkyl group having 1 to 20 carbon atoms. The alkyl group may be linear, branched, or cyclic. Examples of the linear and branched alkyl groups include alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-butyl group, an iso-butyl group, and a tert-butyl group. Examples of the cyclic alkyl group include cyclic alkyl groups having 6 to 10 carbon atoms, such as a cyclohexyl group and an isobornyl group. One or more hydrogen atoms of this alkyl group may be substituted with other groups. The substituents of the alkyl group include a hydroxyl group, an aryloxy group such as a phenyloxy group, an aryl group such as a phenyl group, an epoxy group, an aliphatic heterocyclic compound residue such as a tetrahydrofuryl group, an amino group (-R 3 R 4 :R 3 , R 4 each independently represents an alkyl group having 1 or 2 carbon atoms. The number of carbon atoms in the substituted alkyl group is preferably 1 or more and 3 or less. Specific examples of the vinyl compound represented by formula (2) include: Methyl (meth)acrylate (Tg': 281K or 378K), Ethyl methacrylate (Tg': 338), n-Butyl methacrylate (Tg': 293), Isobutyl methacrylate (Tg': 321), n-Stearyl (meth)acrylate (Tg': 303 or 311), tert-Butyl (meth)acrylate (Tg': 314 or 380K), Cyclohexyl (meth)acrylate (Tg': 288 or 339K), Isobornyl (meth)acrylate (Tg': 367 or 453K), Benzyl (meth)acrylate (Tg': 279K or 327K), 2-Hydroxyethyl methacrylate (Tg': 328K), 2-Hydroxypropyl methacrylate (Tg': 299), (Meth)acrylate (Tg': 379K or 417K), 2-hydroxy-3-phenoxypropyl acrylate (Tg': 290K), N,N-Dimethylaminoethyl (meth)acrylate (Tg': 392K or 291K), N,N-diethylaminoethyl methacrylate (Tg': 293K), Glycidyl methacrylate (Tg': 319K), Tetrahydrofurfuryl methacrylate (Tg': 333K) etc. can be mentioned.
[0030] [ka]
[0031] (In the formula, R 5 and R 6 each independently represents a hydrogen atom or a methyl group, R 7 represents an alkylene group having 4 to 10 carbon atoms. In formula (3), R 5 and R 6 are preferably the same group. Specific examples of the vinyl compound represented by formula (3) include: Neopentyl glycol di(meth)acrylate (Tg': 390K or 305.5K), 3-Methyl-1,5 pentanediol diacrylate (Tg': 378K), 1,6-Hexanediol diacrylate (Tg': 336K), 1,9-Nonanediol diacrylate (Tg': 341K) etc. can be mentioned. An example of the vinyl compound having a (meth)acryloylamide group is a compound represented by the following formula (4) and having a Tg' in the above specific range.
[0032] [ka]
[0033] (In the formula, R 8 represents a hydrogen atom or an alkyl group, and R 9 is an amino group (-R 10 R 11 :R 10 , R 11 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; R 10 , R 11may be bonded to form an aliphatic heterocyclic compound residue such as a morpholinyl group. Specific examples of the vinyl compound represented by formula (4) include: Acryloylmorpholine (Tg': 418K), N,N-dimethylacrylamide (Tg': 119K), N,N-diethylacrylamide (Tg': 354K), N-isopropylacrylamide (Tg': 407K) etc. can be mentioned.
[0034] The Tg' of a monomer is a glass transition temperature measured by a standard method using a homopolymer obtained by homopolymerization of the monomer. As the Tg' of a monomer, a value measured by a differential scanning calorimeter (DSC) according to a method conforming to JIS K7121-1987 or JIS K 6240, or a catalog value can be used. A monomer (A) that gives a Tg' in the above-mentioned specific range is selected for use in the present invention. HTg In addition, the Tg' value of the above compound is written in the parentheses next to the monomer (A HTg ) are shown as reference values when selecting a
[0035] Generally, for easily adherent materials such as stainless steel (SUS), adhesive strength is stronger than the ease with which the material sticks to the substrate (tack), so a lower adhesion index (an adhesion index lower than 1.5) will result in better adhesion. On the other hand, for poorly adhesive resins such as POM, the ease with which the material sticks to the substrate (tack) has a stronger effect than adhesive strength, so the higher the adhesion index, the better the adhesion. However, if the adhesion index is too high, the holding power decreases and adhesiveness cannot be exerted, so it is necessary to adjust the value appropriately. In this invention, the adhesion index and properties of various acrylic copolymers against POM were compared, and it was found that the appropriate adhesion index for excellent adhesion, high temperature retention, load resistance, and impact resistance even to poorly adhesive resins such as POM is 1.5×10 -2 Above 2.0×10 -2Furthermore, the inventors compared the properties of acrylic copolymers having various monomer compositions against POM and found that acrylic copolymer (A) has excellent adhesion, high temperature retention, load resistance, and impact resistance even to poorly adhesive resins such as POM.
[0036] In the present invention, the weight average molecular weight of the acrylic copolymer is preferably from 650,000 to 1,200,000, and the monomer (A HTg The desired effect is achieved by selecting and combining a content ratio of 11.5 mass % or more and an adhesion index within the above range. For reference, the adhesion index of the acrylic copolymer in each synthesis example of Patent Document 1 is in the range of 1.18 to 1.48 and in the range of 2.30 to 3.62. Although the examples of Patent Documents 2 and 3 disclose acrylic copolymers whose adhesion indexes satisfy the above ranges, these acrylic copolymers do not meet the above three requirements ("range of weight average molecular weight" and "monomer (A HTg There is no disclosure of an acrylic copolymer that simultaneously satisfies the "content ratio of the component (I))" and the "range of adhesion index." The adhesion index of the acrylic copolymer in each example of Patent Document 4 is in the range of 2.22 to 2.90.
[0037] (Crosslinking agent) Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, amine-based crosslinking agents, etc. Among these, isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and metal chelate-based crosslinking agents are preferred. Specific examples of isocyanate-based crosslinking agents include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate; aromatic isocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate and xylylene diisocyanate; and isocyanate adducts such as trimethylolpropane / tolylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HL"), and isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HX"). The content of the isocyanate-based crosslinking agent is typically from 0.1 to 20 parts by mass, more preferably from 0.5 to 10 parts by mass, based on 100 parts by mass of the acrylic copolymer (A). Examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Company, Inc., product name "Tetrad C"), N,N,N',N'-tetraglycidyl-m-xylylenediamine (manufactured by Mitsubishi Gas Chemical Company, Inc., product name "Tetrad X"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Company, Inc., product name "Epolite 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Company, Inc., product name "Epolite 1600"). Co., Ltd., trade name "Epolite 1500NP"), ethylene glycol diglycidyl ether (Kyoeisha Chemical Co., Ltd., trade name "Epolite 40E"), propylene glycol diglycidyl ether (Kyoeisha Chemical Co., Ltd., trade name "Epolite 70P"), polyethylene glycol diglycidyl ether (NOF Corporation, trade name "Epiol E-400"), polypropylene glycol diglycidyl ether (NOF Corporation, trade name "Epiol P-200"), sorbitol polyglycidyl ether (Nagase ChemteX Corporation, trade name "Denacol" Examples of the epoxy crosslinking agent include glycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-611"), glycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-314"), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-512"), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. The content of the epoxy crosslinking agent is 0.01 parts by mass or more and 10 parts by mass or less, more preferably 0.03 parts by mass or more and 5 parts by mass or less, based on 100 parts by mass of the acrylic copolymer (A). As the metal chelate crosslinking agent, for example, a metal chelate compound in which the metal atom is aluminum, zirconium, titanium, zinc, iron, tin, etc., can be used. Among them, an aluminum chelate compound or a titanium chelate compound is preferable. Examples of aluminum chelate compounds include diisopropoxyaluminum monooleyl acetoacetate, monoisopropoxyaluminum bisoleyl acetoacetate, monoisopropoxyaluminum monooleate monoethyl acetoacetate, diisopropoxyaluminum monolauryl acetoacetate, diisopropoxyaluminum monostearyl acetoacetate, diisopropoxyaluminum monoisostearyl acetoacetate, monoisopropoxyaluminum mono-N-lauroyl-β-alanate monolauryl acetoacetate, aluminum tris(acetylacetonate), acetylacetonate aluminum bis(ethyl acetoacetate), monoacetylacetonate aluminum bis(isobutyl acetoacetate) chelate, monoacetylacetonate aluminum bis(2-ethylhexyl acetoacetate) chelate, monoacetylacetonate aluminum bis(dodecyl acetoacetate) chelate, and monoacetylacetonate aluminum bis(oleyl acetoacetate) chelate. Examples of titanium chelate compounds include titanium diisopropoxybis(acetylacetonate), titanium tetra-n-butylate, titanium tetra-2-ethylhexanoate, titanium tetraacetylacetonate, titanium diisopropoxybis(ethylacetoacetate), and titanium octylene glycolate. Other examples of the metal chelate compounds include zirconium tetraacetylacetonate and zirconium tributoxymonoacetylacetonate. The above metal chelate crosslinking agents may be used alone or in combination of two or more. The content of the metal chelate crosslinking agent is typically from 0.01 to 10 parts by mass, more preferably from 0.03 to 7 parts by mass, and even more preferably from 0.05 to 5 parts by mass, relative to 100 parts by mass of the acrylic copolymer (A).
[0038] (Polymerization method) The acrylic copolymer (A) is obtained by copolymerizing each of the monomers described above. The polymerization method is not particularly limited, but radical solution polymerization or radical emulsion polymerization is preferred from the viewpoint of ease of polymer design. Alternatively, an acrylic syrup consisting of the acrylic copolymer (A) and its monomers may be first prepared, and then a crosslinking agent and an additional photopolymerization initiator may be added to the acrylic syrup to polymerize it.
[0039] (tackifier) The adhesive composition may contain a tackifier (C) as necessary for the purpose of adjusting the adhesive strength, etc. Specific examples of the tackifier include tackifier resins such as rosin-based resins, terpene-based resins, petroleum-based resins, alkylphenol resins, xylene-based resins, and other resins. These may be used in combination of two or more. Among these, rosin-based resins and xylene-based resins are particularly preferred. The softening point of the tackifier is preferably at least 125° C., and more preferably at least 135° C. This softening point is a value measured in accordance with JIS K 2531 (ring and ball method). Examples of the rosin-based resin include hydrogenated resin, disproportionated resin, polymerized ester resin, etc. Examples of the terpene-based resin include terpene phenol resin, α-pinene-based resin, β-pinene-based resin, etc. Examples of the petroleum-based resin include aliphatic resin, aromatic resin, etc. The ratio of the tackifier (C) to 100 parts by mass of the acrylic copolymer (A) can be selected from preferably 0 parts by mass or more and 15 parts by mass or less, more preferably 0 parts by mass or more and 12 parts by mass or less. If the amount of the tackifier added is more than 15 parts by mass, the high temperature retention may decrease. When the tackifier is used, the lower limit of the content is not particularly limited and can be set appropriately, but it can be 1 part by mass or more to 100 parts by mass of the acrylic copolymer (A).
[0040] (fillers, pigments) The pressure-sensitive adhesive composition of the present invention may further contain at least one of various additives such as an inorganic filler, a light-shielding filler, and a pigment. The ratio of the filler or pigment to 100 parts by mass of the acrylic copolymer (A) can be selected from the range of 0.1 parts by mass or more and 100 parts by mass or less. Specific examples of the inorganic filler include silica, calcium carbonate, and alumina. Specific examples of the light-shielding filler include carbon black, carbon nanotubes, and black inorganic fillers. Specific examples of pigments include carbon black, aniline black, acetylene black, and ketjen black.
[0041] <Adhesive tape> The pressure-sensitive adhesive tape of the present invention has a pressure-sensitive adhesive layer containing the above-mentioned pressure-sensitive adhesive composition. The adhesive tape can be provided as a so-called "baseless type" tape, which consists only of an adhesive layer when in use, or as a tape having an adhesive layer on at least one surface of a substrate, in which the substrate and adhesive layer are used together as one unit. 1(a) to (c) are diagrams showing one embodiment of a pressure-sensitive adhesive tape according to the present invention. The pressure-sensitive adhesive tape shown in FIG. 1(a) is a single-sided pressure-sensitive adhesive tape, and has a pressure-sensitive adhesive layer 2 formed from a pressure-sensitive adhesive composition according to the present invention on the upper surface (side A) of a tape-shaped substrate 1. The adhesive tape shown in FIG. 1(b) is a double-sided adhesive tape having adhesive layers 2-1, 2-2 on both sides (upper surface: side A and lower surface: side B) of a tape-like substrate 1, at least one of the two adhesive layers being an adhesive layer formed from the adhesive composition of the present invention. The adhesive tape shown in FIG. 1(c) is a baseless type adhesive tape, and is composed of an adhesive layer 2 only. These pressure-sensitive adhesive tapes can be produced by known methods, including a typical method of uniformly applying a pressure-sensitive adhesive composition onto a support for forming a pressure-sensitive adhesive layer, and then allowing a crosslinking reaction to form a pressure-sensitive adhesive layer. By using a support serving as the substrate 1 shown in FIGS. 1(a) and (b) for forming a pressure-sensitive adhesive layer, the pressure-sensitive adhesive layer can be formed directly on the substrate. Alternatively, the adhesive layer formed on a support for forming the adhesive layer can be transferred and attached to the substrate 1 shown in Figs. 1(a) and (b) to form the adhesive layers 2, 2-1, and 2-2. The adhesive tape can be efficiently produced by using a sheet-like support for forming the adhesive layer, and cutting and dividing the adhesive layer formed on the support into the desired tape shape. The baseless type adhesive tape shown in FIG. 1(c) can be obtained by transferring an adhesive layer formed on a support onto a release liner. As the support for transfer, release paper, a plastic film having a release surface, or the like can be used. For the crosslinking reaction of the pressure-sensitive adhesive composition on the support for forming the pressure-sensitive adhesive layer, a crosslinking reaction caused by heating and / or ultraviolet irradiation can be utilized.
[0042] 1(a), surface A of the substrate 1 may be subjected to a surface treatment such as a corona discharge treatment, or may be provided with an undercoat layer, or both, as required, thereby improving the adhesion of the pressure-sensitive adhesive layer 2 to the substrate 1. 1(a), a release layer can be provided on side B of the substrate 1, if necessary. This prevents the pressure-sensitive adhesive layer 2 from being transferred to side B of the substrate 1 when the pressure-sensitive adhesive tape is wound into a roll, and also makes it easy to unwind the tape. At least one of the sides A and B of the substrate 1 in Fig. 1(b) may be subjected to a surface treatment such as a corona discharge treatment, provided with an undercoat layer, or both, thereby improving the adhesion of the pressure-sensitive adhesive layer 2-1 and / or the pressure-sensitive adhesive layer 2-2 to the substrate 1. The thickness of the pressure-sensitive adhesive layer is preferably 5 μm or more and 100 μm or less, and more preferably 10 μm or more and 80 μm or less. Examples of materials constituting the substrate 1 include plastic films, metal foils, paper, woven fabrics, nonwoven fabrics, and foams. Two or more of these may be used in combination. Examples of materials constituting the plastic films for the substrate include polyether ether ketone (PEEK), polyimide (PI), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), biaxially oriented polypropylene (OPP), polyphenylene fide (PPS), and the like. Examples of materials that can be used to form the foam include urethane, polyethylene (PE), and polypropylene (PP). EXAMPLES
[0043] The present invention will be described in more detail below with reference to examples and comparative examples. In the following description, "parts" means parts by mass and "%" means % by mass. [Preparation of acrylic copolymer (A)] In a reactor equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube, the monomer components shown in Tables 1 and 2, ethyl acetate as a solvent, n-dodecanethiol as a chain transfer agent and 0.1 parts of peroyl L as a radical polymerization initiator were charged. Nitrogen gas was sealed in the reactor, and the polymerization reaction was carried out at 68°C for 3 hours under a nitrogen gas stream while stirring, and then at 78°C for 3 hours at a polymerization concentration of 50%. After that, the mixture was cooled to room temperature and an antioxidant was added. As a result, an acrylic copolymer (A) was obtained.
[0044] The numerical values attached to each component in the table indicate the amount (%) of each component, and the abbreviated compound names of each component are as follows: 2-EHA: 2-Ethylhexyl acrylate "AA": Acrylic acid "BA": n-Butyl acrylate "MA": Methyl acrylate "Vac": Vinyl Acetate 4-HBA: 4-Hydroxybutyl acrylate 2-HEA: 2-Hydroxyethyl acrylate Among the above monomer compounds, "AA", "MA", and "Vac" are monomers with Tg' in the range of 273K to 437K (A HTg ) and the Tg' of other monomers is outside this range.
[0045] In Examples 1 to 5, the monomer composition and polymerization degree were determined based on the adhesion index of 1.5×10 -2 Above 2.0×10 -2 It was adjusted as follows: In Comparative Example 1, the monomer composition and polymerization degree were set to a value of 2.0×10 -2 The results were adjusted to be as above. In Comparative Examples 2 to 5, the monomer composition and polymerization degree were adjusted to a value of 1.5×10 -2 It was adjusted as follows:
[0046] [Preparation of adhesive tape] 100 parts of the solid content of acrylic copolymer (A) prepared using each monomer composition shown in Tables 1 and 2 was mixed with 1.3 parts of Coronate L (manufactured by Nippon Polyurethane Co., Ltd., product name Coronate L: solid content concentration 45%) as a crosslinking agent to prepare a pressure-sensitive adhesive composition. This adhesive composition was applied onto a silicone-treated release paper having a thickness of about 0.12 mm so that the thickness of the adhesive composition after drying was 0.05 mm. Next, the solvent was removed and the adhesive was dried at 110°C for 2 minutes, and a crosslinking reaction was carried out. Then, a crosslinking reaction was carried out for 2 minutes using an infrared heater set so that the effective temperature of the infrared heater was 105°C or higher and 110°C or lower, to form an adhesive layer. This adhesive layer was attached to both sides of a corona discharge-treated polyolefin material sheet substrate having a thickness of 0.15 mm. Then, the adhesive was cured at 40°C for 3 days to obtain a double-sided adhesive tape having an adhesive layer having a thickness of 0.05 mm. The numerical values attached to each component in the table indicate the amount (parts) used, and the compound names of each component are as follows: "Coronate L": Isocyanate-based crosslinking agent (manufactured by Nippon Polyurethane Co., Ltd., product name: Coronate L)
[0047] <Evaluation test> The pressure-sensitive adhesive tapes obtained in each of the Examples and Comparative Examples were evaluated by the following methods, and the evaluation results are shown in Tables 1 and 2. (Adhesive strength) The adhesive strength was measured using a test method in accordance with JIS Z 0237:2000, and was evaluated according to the following criteria: The adherends used were a stainless steel plate (SUS304BA plate), a POM plate (POM (NC) manufactured by Toray Plastics Precision Co., Ltd.), and a polycarbonate plate (PC1600 manufactured by Takiron C.I. Co., Ltd.) (these are referred to as "SUS", "POM", and "PC plate" in Tables 1 and 2, respectively). △: Less than 5N / 10mm ○: 5N / 10mm or more, less than 10N / 10mm ◎: 10N / 10mm or more In this evaluation standard, it is desirable that there be no zipping and that the evaluation be ◯ or better. (shock resistance) The impact resistance was measured using the DuPont impact resistance test method. That is, as shown in Fig. 2(a), the adhesive tape was cut into a frame shape so that the rectangular planar shape was L2 (horizontal) = 45 mm, L1 (vertical) = 50 mm, and the peripheral part of the rectangle with W (width) 1 mm remained, to prepare a measurement sample 6. Fig. 2(b) shows a schematic overview of the testing machine. In Fig. 2(b), the sample 6 and the adherends 5 and 7 are shown as cross-sectional views in the thickness direction. As shown in Fig. 2(b), a 100g jig 4 is attached, and a 200g weight 3 is dropped from it three times from each height of 100mm, 125mm, 150mm, 175mm, ... until the adherend (glass plate) 7 on the lower side falls. The combination of adherends was a perforated PC board (manufactured by Takiron C.I. Co., Ltd., PC1600) (thickness 4 mm × width 50 mm × height 100 mm (with a 40 mm × 40 mm square window cut out in the center) 5 and a glass plate 7 (manufactured by Asahi Glass Co., Ltd., FL2) (thickness 1.9 mm × width 50 mm × height 60 mm), and the glass plate 7 was set up so that it was facing downward. The impact resistance was evaluated according to the following criteria based on the height of the weight when the adherend was dropped. ×: Falls at 100mm △: Falls at 125mm ○: Falls at 150mm ◎: Falls 175mm or more In this evaluation standard, an evaluation result of ◯ or higher is desirable. (tack) The tack was measured using a test method in accordance with JIS Z 0237. The inclination angle was set to 10°. Based on the measured values, the tackiness was evaluated according to the following criteria. ×: Less than 5 △: 5 or more but less than 10 ○: 10 or more and less than 15 ◎: 15 or more In this evaluation standard, an evaluation result of ◯ or higher is desirable. (Load bearing capacity) Regarding the load-bearing capacity, as shown in Figure 3, an L-shaped jig 9 (25 g) made of SUS304 was attached to an adherend (POM plate or polycarbonate plate) with adhesive tape 8 (10 mm × 10 mm; substrate 8a, adhesive layer 8b), and left to stand at 90°C, and the time until it fell was measured. The load resistance, which is an index of high temperature retention, was evaluated based on the measured values according to the following criteria. △: Less than 5 minutes ○: 5 minutes or more but less than 10 minutes ◎: 10 minutes or more In this evaluation standard, an evaluation result of ◯ or higher is desirable.
[0048] [Table 1]
[0049] [Table 2] [Industrial Applicability]
[0050] The pressure-sensitive adhesive composition of the present invention has excellent adhesion to resin materials suitable for 5G, which are used in portable electronic devices, automotive sensors, and recorders as mobile communication systems move to 5G, in particular to poorly adhesive resins such as POM, and is useful as a pressure-sensitive adhesive composition or adhesive tape for attachment to such materials or for fixing members using such materials.
Claims
1. A pressure-sensitive adhesive composition comprising an acrylic copolymer (A) and a crosslinking agent (B), The acrylic copolymer (A) has a weight average molecular weight of 650,000 or more and 1,200,000 or less, and a monomer (A) having a Tg' (glass transition temperature when the monomer is homopolymerized) of 273 K or more and 437 K or less in all monomer components of the acrylic copolymer (A). HTg ) is 11.5 mass% or more, The theoretical glass transition temperature (theoretical Tg) of the acrylic copolymer (A) is a, and the weight average molecular weight (×10 4 ) in the total monomer components (A HTg The content ratio of each of the above is expressed by the following formula (1): [0010] The adhesion index expressed as 1.5 x 10 -2 Above 2.0 x 10 -2 is as follows: the acrylic copolymer (A) is an acrylic copolymer having a carboxyl group and a hydroxyl group, the monomer components of the acrylic copolymer (A) contain, based on 100 mass% of all monomer components, 70 mass% or more and 90 mass% or less of a (meth)acrylic acid alkyl ester (A1) having an alkyl group having 4 to 12 carbon atoms, 3 mass% or more and 7 mass% or less of a (meth)acrylic acid alkyl ester (A2) having an alkyl group having 1 to 3 carbon atoms, 5 mass% or more and 8 mass% or less of a carboxyl group-containing monomer (A3), and 0.1 mass% or more and 0.2 mass% or less of a hydroxyl group-containing monomer (A4); Adhesive composition.
2. The pressure-sensitive adhesive composition according to claim 1, wherein the acrylic copolymer (A) has a theoretical Tg of 223 K or less.
3. The pressure-sensitive adhesive composition according to claim 1, wherein the total content of the carboxyl group-containing monomer (A3) and the hydroxyl group-containing monomer (A4) is 10.5 mass% or less.
4. The pressure-sensitive adhesive composition according to claim 1, wherein the monomer components of the acrylic copolymer include a vinyl compound monomer (A5) other than the monomer components (A1) to (A4).
5. The pressure-sensitive adhesive composition according to claim 1, wherein the monomer components of the acrylic copolymer contain 10 mass % or less of a vinyl compound monomer (A5) other than the monomer components (A1) to (A4).
6. An adhesive tape having an adhesive layer formed from the adhesive composition according to any one of claims 1 to 5.
7. The pressure-sensitive adhesive tape according to claim 6 , comprising a sheet-like substrate and a pressure-sensitive adhesive layer provided on at least one surface of the sheet-like substrate.
Citation Information
Patent Citations
Fine displacement table apparatus
JP1988007175A
Pressure-sensitive adhesive tape
JP2011006608A
Adhesive for optical element
JP2012001647A
Adhesive tape for sealing food container
JP2013163746A
Optical adhesive composition, optical adhesive sheet and picture display unit
JP2015151514A